BACKCHANNELS IN THE INTERACTIONS OF INDONESIAN L2 SPEAKERS OF ENGLISH IN AUSTRALIAN ACADEMIC CONTEXT - Purwanti, Indah Tri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
This study investigated backchannels, short verbal responses such as yeah, employed by Indonesian L2 speakers of English in the interactions with L1 speakers of Australian English in Australian academic setting. The naturally occurring dyadic interactions were audiotaped and scrutinised in a sequential analysis of conversation analysis. The examination was aimed to scrutinise the pragmatic functions and the placement of backchannels within the sequential organisation of the interactions. The findings showed that they used backchannel responses involving non-lexical items, lexical items, and combinations of lexical and non-lexical items. Backchannel responses existed in different linguistic environments that may be culturally specific such as after you know. Backchannels were used to show attentiveness, agreement, and comprehension of the speaker’s talk. Besides, they also employed backchannels to express politeness to satisfy the supervisors’ positive face in the interactions. In this study, they appear to converge their linguistic devices to that of their supervisors.